Cytotoxicity and residual effect of ethanol extract of pequi peel on canine osteosarcoma cells (Research, Society and Development, 2020)
The development of new chemotherapy drugs is a premise for the scientific community in recent years, mainly through the use of plants and other natural sources. In this context, analyses of cytotoxicity and residual effect have become essential for the establishment of new therapies. Therefore, this study aims to evaluate the cytotoxic and residual effects of ethanol extract of pequi peel (EEPP) on canine osteosarcoma cells. For this, we used analyses of cell viability, cytotoxicity, IC50, and cell survival after therapy in treatments of 24, 48, and 72 hours. We used the design of the randomized block, using an Analysis of Variance with Tukey’s posthoc test to compare the treatments, considering a 5% significance. The extract showed no cytotoxic effect within 24 hours of treatment, but a protective effect, or possibly a mitotic-inducing effect on osteosarcoma cells. However, at 48 and 72 hours, we found gradual cytotoxicity favoring the effective control of neoplastic cells, obtaining, on average, 55% of cytotoxicities at concentrations of 10 to 100 µg/mL. IC50 values were 4.05 µg/mL for the 48-hour group and 4.53 µg/mL for the 72-hour group. The treatment residual effect reduced cell growth after the exposure to the extract. The survival factor was lower (18.81%) in the 72-hour group, with a concentration of 10 µg/mL and higher (81.33%) in the 48-hour group, with a concentration of 100 µg/mL. These results suggest that the ethanol extract of pequi peel promotes the increase in cell viability within 24 hours, cytotoxic action in exposures over 48 hours, and time-dependent residual effect on canine osteosarcoma cells.